2012
DOI: 10.2337/dc12-0455
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin Predicts Cardiovascular Outcome in Hemodialysis Patients With Type 2 Diabetes

Abstract: OBJECTIVEBMI and albumin are commonly accepted parameters to recognize wasting in dialysis patients and are powerful predictors of morbidity and mortality. However, both parameters reveal limitations and may not cover the entire range of patients with wasting. The visceral protein transthyretin (TTR) may be helpful in overcoming the diagnostic and prognostic gap. Therefore, the aim of this study was to assess the association of TTR with morbidity and mortality in hemodialysis patients.RESEARCH DESIGN AND METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Several studies have suggested the use of serum prealbumin as a better surrogate of nutritional status and cardiovascular outcome and a predictor of mortality in patients with maintenance HD [5] , [7] , [16] , [18] . The cumulative survival of HD patients with prealbumin > 30 mg/dL was significantly better than that of patients with prealbumin < 30 mg/dL [12] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested the use of serum prealbumin as a better surrogate of nutritional status and cardiovascular outcome and a predictor of mortality in patients with maintenance HD [5] , [7] , [16] , [18] . The cumulative survival of HD patients with prealbumin > 30 mg/dL was significantly better than that of patients with prealbumin < 30 mg/dL [12] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Prealbumin, a marker for protein malnutrition, has been advocated as a useful marker for predicting gastric surgery complications, cardiovascular outcome, and mortality in diabetic hemodialysis patients [ 10 , 11 ]. To our knowledge, there is no available study on the patterns or prognostic value of prealbumin levels in patients with DKA and DK.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we aimed to evaluate changes in prealbumin levels and their diagnostic value in reflecting the severity of hyperglycemic emergencies. It should be stressed that previous studies only provided limited information and did not characterize the correlation with hyperglycemic crises [ 5 , 10 , 11 ]. The current study was performed due to limitations of the existing data in the literature.…”
Section: Introductionmentioning
confidence: 99%
“… 16 18 The TTR tetramer concentration in human plasma varies from ≈3.4 to 5 μM. 19 , 20 Following rate-limiting tetramer dissociation and partial monomer denaturation, TTR can aggregate via a downhill polymerization mechanism to form fibrillar cross-β-sheet, or amyloid, deposits, as well as a spectrum of structurally diverse aggregates. 12 , 21 24 Dissociation of TTR tetramers begins by dimer separation along the weaker dimer–dimer interface comprising the thyroxine binding sites (Figure 1 A).…”
mentioning
confidence: 99%